The role of psychological and social factors in the relationship between attachment and suicide: A systematic review. (20th April 2020) - Green, Jessica; Berry, Katherine; Danquah, Adam; Pratt, Daniel
Abstract : Insecure attachment is widely accepted to be a risk factor for suicidal thoughts and behaviour. To increase our understanding of this distal association, the current systematic review aimed to evaluate empirical evidence that has investigated the role of psychosocial mechanisms within this relationship. Sixteen original research articles were identified, with the majority carrying out mediational analyses to test their hypotheses. Substantial heterogeneity was found across studies with regards to their theoretical approach to assessing attachment, suicide‐related outcomes, sample population, statistical analyses, and the psychological factors under investigation. Nevertheless, this emergent evidence base indicates that a range of predisposing, precipitating, and crisis‐state factors may mediate the association between attachment security and suicidality. Studies that investigated moderating factors did not report significant findings, and the mediating role for psychiatric diagnoses remains unclear. Furthermore, this emerging research base is limited by an over‐reliance on cross‐sectional designs and self‐reported data. Longitudinal and experimental designs are required to verify causal pathways and to investigate whether trait vulnerabilities interact with acute stressors to increase suicide risk. Finally, disorganized attachment has been overlooked so far and should be given greater consideration going forward.